The management modeling of ecological and economic system - Us, Svetlana; Tymoshenko, Liubov (My University, 2024)
The authors conducted a study of the ecological and economic system on the example of the company of the fuel and energy complex
Моделювання управління еколого-економічною системою
Keywords: cognitive modeling; cognitive map; ecological and economic system; environmental and economic indicators